PENGARUH PENGGUNAAN KOAGULAN ALAMI SARI BELIMBING WULUH PADA TAHU PUTIH BERDASARKAN PERBEDAAN KONSENTRASI DAN LAMA PENGGUMPALAN - Sansi, Delfira Hisana; Wahyudi, Vritta Amroini; Elianarni, Dahlia (Food Technology and Halal Science Journal, 2024)
Tofu is a food whose process involves agglomerating soybean curd using coagulants, one of which is vinegar. In addition, from the other side, vinegar acid has shortcomings so that a natural coagulant substitute such as starfruit wuluh is needed. Belimbing wuluh one of the fruits that contains citric acid so that it can be used as a natural coagulant to replace vinegar, besides that it also contains oxalic acid, acetic acid, malic acid, formic acid, ascorbic acid and other compound components. This study aims to determine the effect of star fruit juice concentration and clotting time on the physicochemical and organoleptic properties of white tofu using star fruit as a coagulant. The method used was Randomized Group Design (RGD) using two factors, namely the concentration of Wuluh starfruit juice (factor 1) consisting of 4%, 5% and 6% and the coagulation activity (factor 2) consisting of 20 minutes, 30 minutes and 40 minutes. The testing parameters include protein content, fat content, moisture content, ash content, carbohydrate content, chewiness and organoleptic (scent, taste, color, texture and liking). The results of the analysis showed that there was an effect of the use of star fruit juice concentration and clotting time on protein in white tofu, which ranged from 3.50% - 6.77%; the range of water content ranged from 85.79% - 89.89%, chewiness was 3.08 N - 16.03 N. However, there was no significant effect on ash, fat and carbohydrates. As for the organoleptic test, the results showed a significant effect for scent parameters ranging from 2.80 (somewhat fragrant) - 4.05 (fragrant), color ranging from 2.45 (not bright white) - 3.45 (slightly bright white), texture ranging from 2.85 – 3,65 (slightly chewy) and liking ranging from 3.05 (slightly like) - 3.7 (like).